Some Problems in Understanding and Explaining the Science of Philosophy - Panjiev, Suhrob (European Journal of Life Safety and Stability (2660-9630), 2021)
In the state rassmatrivayutsya some problems of understanding and interpretation of philosophical science, in frequency, differences between philosophies and philosophical studies, philosophical content of ethical concepts and concrete dialectical relations.